Understanding Toxoplasma gondii transmission in an ecological context—the contribution of wild avian species from urban environments - Penezić, Aleksandra; Uzelac, Aleksandra; Breka, Katarina; Simin, Stanislav; Ovari, Kristijan; Pantelić, Ilija; Ćirković, Vladimir; Ćirović, Duško; Klun, Ivana (Frontiers in Veterinary Science, 2025)
IntroductionThe role of avians in the transmission chain of Toxoplasma gondii, a zoonotic coccidian parasite of the phylum Apicomplexa, is as intermediate hosts. However, the true contribution and significance of wild species in the maintenance and spread of the parasite in different ecosystems is not well understood.MethodsFor this study, heart tissue of 224 individual birds, representing 15 common wild species, and one domestic, Gallus gallus domesticus (backyard chickens), was collected. Total nucleic acids were extracted and the presence of T. gondii gDNA was ascertained by amplification of the 529 bp repeat element.ResultsThe infection was detected in 24.1% of the wild birds and in 41.4% of backyard chickens. The occurrence of infection in wild species did not statistically differ by diet or among urban (22.4%), peri-urban (27.3%) and rural areas (22.7%); in contrast, a statistically significant difference was observed between peri-urban (21%) and rural (80%) backyard chickens. Among the 11 city dwelling species, wood pigeons (Columba palumbus), rooks (Corvus frugilegus) and hooded crows (Corvus cornix) were the most numerous. The frequency of infection in the two corvid species was 32.1% and 31.6% in rooks and hooded crows, respectively, and 15.6% in wood pigeons, suggesting that corvids may be good bioindicators for the parasite in cities. As the majority (84%) of the city dwelling birds originated from a single residential area, possible local natural reservoirs of T. gondii, rodents and water, were analyzed additionally. Of the 16 rodents, 56.2% were infected, while three out of four samples of river water harbored T. gondii gDNA, indicating a fairly high probability of exposure to the parasite.DiscussionCollectively, our findings show that diet may not be a primary risk for T. gondii infection. Instead, the importance of understanding prevalence in birds in an ecological context and the contribution of environmental factors in different habitats are highlighted.